The role of emotional and cognitive engagement in refugee entrepreneurship and business sustainability: Evidence from Ghanaian SMEs - Samuel Oduro Owusu; Mathew Thomas Gil (Cogent Business & Management)
This study investigated the role of cognitive and emotional engagement in refugee entrepreneurship and business sustainability. Based on the Mixed Embeddedness Theory and Kahn’s Theory of Engagement, data were collected via a close-ended questionnaire distributed to 259 refugee-owned businesses in Greater Accra-Ghana. Using Smart PLS SEM (4) for data analysis and path modeling, the findings reveal that refugee entrepreneurship significantly and positively affects business sustainability. Emotional and cognitive engagement partially mediate this relationship, thus influencing the link between refugee entrepreneurship and sustainability. This study highlights cognitive and emotional engagement as pivotal mechanisms enabling refugee entrepreneurs to navigate complex environments and sustain their ventures. By integrating the Mixed Embeddedness Theory and Kahn’s Theory of Engagement, this study offers novel insights into how refugee entrepreneurs overcome socioeconomic barriers to sustain their businesses. This study contributes to research and practice by emphasizing the distinct and combined impact of cognitive and emotional engagement on refugee entrepreneurship and sustainability. It recommends that policymakers design cognitive programs focused on problemsolving, strategic thinking, and innovation, with scenario-based modules to enhance adaptability to market changes.